Reception of Herzen’s “From the Other Shore” in China: problems and prospects - Panxin Ji (RUDN Journal of Studies in Literature and Journalism, 2023)
The history of the reception of Herzen's collection of essays and dialogues “From the Other Shore” (“From Another Shore”) in China from the late 19th century to the present is considered. The objectives of this study are: 1) to identify the timing, background, and mode of the early reception of “From the Other Shore” in China; 2) to analyze the different emphases and factors for its reception in China at different times; 3) to explore the problems, reasons and perspectives in the process of its reception in China. The significance of the research topic lies in the necessity to elucidate the peculiarities of perception of Herzen's work in China, which is closely linked to emerging trends in the Sino-Russian intercivilizational dialogue. The process of reception of the book in China, focusing on translation and counting the socio-cultural transformations that have taken place in China from the end of the Qing Dynasty to the present day, is explored. The evolution of Herzenology (Herzen studies) in China has been characterized by rises and falls, and even the periods of oblivion. This was influenced by both historical changes in Chinese society and the international environment. An important range of issues for modern Herzen studies is highlighted: the basics of the interest of Chinese intellectuals to Herzen's book in the early 20th century; the main directions of Chinese scholars' research on this collection of political essays; the reasons for the prolonged neglect of the book by Chinese academics since the late 1960s; the prerequisites for regained attention among Chinese researchers in the 21st century; the new discoveries of Herzen scholars that enriched the culture of China. This research will be valuable in advancing the understanding of the mechanisms underlying Russian-Chinese literary and cultural dialogue, as well as the impact of Russian classical literature on Chinese literature.